An Experimental Study of the Effects of Audit Structure in Uncertain Task Environments - Bamber, E. Michael; Snowball, Doug (The Accounting Review, 1988)
[This study was designed to provide empirical evidence on the effects of audit structure on audit judgments. Specifically, the study examined differences between structured and unstructured audit methods in terms of judgment consensus and auditors' use of coordination and control mechanisms, under different degrees of task uncertainty. A field experiment was conducted involving 113 audit seniors from four firms: two from each end of an audit structure scale. Contrary to expectations, auditors from structured firms did not exhibit uniformly greater consensus in their judgments. However, relative to unstructured firms' auditors, the auditors from structured firms exhibited a greater propensity to increase their use of certain control and coordination mechanisms (especially consultation with peers and audit managers) as the level of task uncertainty increased.]